Genes or nurture? Discussion of the wrong question - Arkadiusz Wąsiński (Studia z Teorii Wychowania)
The paper presents a polemics with a thesis formulated by J. Harris that group socialization theory is an alternative to family nurture. The thesis, indeed, “annihilates” the nurture category and the existing achievements of education sciences off the scientific discourse. The text focuses on an analysis of consistency of arguments regarding the main aspects of the theory in question, identified at four levels of tensions between: genes and environment, child and adult, family and peer group, and being raised in the family and socialization in peer group. The inconsistencies and overinterpretations, expressed by J. Harris in her “systemic” depreciation of child-rearing, inspired some reflections about the possible roles of nurture viewed in the paradigm of biological and spiritual evolution synthesis.